1996
DOI: 10.1016/s0014-5793(96)01228-8
|View full text |Cite
|
Sign up to set email alerts
|

The MAP kinase cascades are activated during post‐ischemic liver reperfusion

Abstract: We have investigated the involvement of MAP kinase cascades in the response of the liver to post-ischemic reperfusion. Both JNKs and ERKs are activated but the duration and magnitude of the increase in their activities appear to be different. JNK activation is more marked but shorter than that of ERKs. The increase observed in the phosphotyrosine content of the 52 kDa Shc protein, accompanied by an increased amount of co-immunoprecipitated Grb2, and the activation of Raf-1 kinase provide evidence of the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 43 publications
3
62
1
Order By: Relevance
“…Among the most proximal events in liver I/R is MAPK activation. 28,29 Cisplatin can affect MAPK signaling 14 ; therefore, to determine whether cisplatin alters liver I/R-induced MAPK activation, western blots for JNK, ERK, and p38 were performed on livers from mice that had undergone I/R. As before, mice were pretreated 12 hours prior with either NSS or cisplatin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most proximal events in liver I/R is MAPK activation. 28,29 Cisplatin can affect MAPK signaling 14 ; therefore, to determine whether cisplatin alters liver I/R-induced MAPK activation, western blots for JNK, ERK, and p38 were performed on livers from mice that had undergone I/R. As before, mice were pretreated 12 hours prior with either NSS or cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…15 MAPK activation contributes to the inflammatory response following liver I/R. 28,29 Therefore, we examined whether cisplatin alters liver I/R-induced MAPK activation. We found that cisplatin blunts I/R-induced JNK and p38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…It includes SAPKs, which are the target of environmental stress, such as liver ischemia-reperfusion. 12,20,21 Among this group, JNK 1 /SAPK 1 is known to be stimulated in vivo after rat liver transplantation 21 or partial hepatectomy. 46 However, these stress conditions also stimulate TNF-␣, which is known to activate JNKs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ischemia and reperfusion could modulate MAPK activity in perfused rat heart, 40 in rat liver, 20 and in rat hepatocytes after liver transplantation. 21 On the basis of these observations, we became interested in studying the effect of hypoxia-reoxygenation (H/R) stress on the different members of endogenous SAPKs in primary cultured rat hepatocytes.…”
Section: Warm Hypoxia-reoxygenation Of Hepatocytes Differently Modulamentioning
confidence: 99%
“…In a number of cell types, heat shock apparently fails to activate ERK MAPKs but does activate the stress-activated MAPKs such as the JNK MAPKs (3,38). However, these responses are apparently cell type-dependent, and heat shock prevents activation of JNK MAPKs and p38 MAPKs in U937 cells but does activate ERK MAPKs in H56 hepatoma cells, NIH 3T3 fibroblasts, human HeLa cells, human KB carcinoma cells, or during whole animal hyperthermia (41)(42)(43)(44)(45). In all of these examples, the activation of ERK MAPK was not examined beyond an initial 60 min of heat shock, and so any long term effect on signaling pathways was not evaluated.…”
Section: Discussionmentioning
confidence: 99%